How to Handle Online Harassment When It Happens to You - Schriefer, Natalie (Wired, 2024)
41% of adults in the US have been harassed online. If your mentions, inboxes, and DMs are blowing up with hateful comments, here are the technological and psychological tools you need to weather the storm.
Section: tags
Keywords: dept.hhs; how-to; mental health; online harassment; social media; twitter

For Kids in the Hospital, Video Games Are Part of Recovery - Schriefer, Natalie (Wired, 2022)
In-house gaming technology specialists play with and support the youngest patients. Plus, research shows that playtime gives literal health points.
Section: tags
Keywords: charity; dept.hhs; gaming culture; health care; video games

How to Cope With Post-Game Depression - Schriefer, Natalie (Wired, 2022)
Congratulations, you beat your favorite video game. Now it’s time to beat the feelings of emptiness.
Section: tags
Keywords: dept.hhs; gaming culture; mental health; psychology; video games

Twenty-Nine - Furey, Rachel (Baltimore Review, 2019)
Keywords: dept.eng; literary-work

Incision - Furey, Rachel (Flyaway: Journal of Writing & Environment, 2020)
Keywords: dept.eng; literary-work

Weighted Vest - Furey, Rachel (River Styx, 2021)
Keywords: dept.eng; literary-work

Chytrid Fungus - Furey, Rachel (CALYX Journal, 2021)
Keywords: dept.eng; literary-work

Swimming - Furey, Rachel (Sou'wester, 2021)
Keywords: dept.eng; literary-work

A Dolphin in Pain - Furey, Rachel (Nimrod International Journal, 2021)
Keywords: dept.eng; literary-work

CPR - Furey, Rachel (Stone Canoe 16, 2022)
Keywords: dept.eng; literary-work

My Face-Eating Octopus - Furey, Rachel (Harpur Palate, 2023)
Keywords: dept.eng; literary-nonfiction

Sea Wolf Meditation - Sonnenschein, Dana (Spoon River Poetry Review, 2022)
Keywords: dept.eng

Bird Guides (poem) - Sonnenschein, Dana (Thimble Literary Magazine, 2022)
Keywords: dept.eng

How to Paint a Gray Wolf - Sonnenschein, Dana (Weber: The Contemporary West)
Keywords: dept.eng

From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg - Aubry, Gwenaëlle (Columbia Journal, 2021)
From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg
Section: Translation
Keywords: dept.lib

“The Master of Scents” * Fiction * By Vincent Ravalec * Translated by Wendeline A. Hardenberg - Ravalec, Vincent (Aromatica Poetica, 2022)
He was the Master of Scents. He ruled over them, classified them, harnessed them, recombined them, invented them, and above all took care of their dis...
Keywords: dept.lib

Meeting the Dire Wolf – Dana Sonnenschein - Sonnenschein, Dana (panoply, a literary zine, 2021)
Not just heavy bones. The huge skull fleshed, broad across the brow and muzzle, 3” canines, thick neck and body — the wolf of your nightmares and not just one. Thirty. A pack drawn to the sce…
Keywords: dept.eng

Mistress of Snow - Sonnenschein, Dana (Gingerbread House Literary Magazine, 2021)
Hinges creak, and she swirls in the door, puts her finger to blue lips. Cold takes the old woodcutter, eyes open, breath frozen in his beard. But crystals melt in your lashes as you gaze on her gl…
Keywords: dept.eng

[Two Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Ozone Park Journal, 2010)
Keywords: dept.lib

Max Ernst Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Qarrtsiluni Online Literary Magazine, 2011)
Keywords: dept.lib

[Seven Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (The Dirty Goat, 2011)
Keywords: dept.lib

[Five Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (TWO LINES Online, 2012)
Keywords: dept.lib

[Three Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Asymptote, 2012)
Keywords: dept.lib

"Words" Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (One Sentence Poems, 2018)
Keywords: dept.lib

The Matrix and the Machine Translated by Wendeline Hardenberg - Ravalec, Vincent (Asymptote, 2018)
Keywords: dept.lib

Persephone 2014 Translated by Wendeline Hardenberg - Aubry, Gwenaëlle (Asymptote, 2019)
Keywords: dept.lib

Contemporary Art is Internationally Appealing by Vincent Ravalec, translated by Wendeline A. Hardenberg - Gaffey, Marlee (Tupelo Quarterly, 2018)
The challenge was to make appealing something that was not. To transform this godforsaken city, populated by people as indifferent to art as tourists are to the idea of visiting the only historic building—a vague ruin of a castle—in a glamorous destination. After all, what the Guggenheim did for Bilbao could be reproduced […]
Keywords: dept.lib

Edgerton Park (Poem) - Sonnenschein, Dana (Hobo Camp Review, 2020)
Keywords: dept.eng